Crime, punishment and the measurement of poverty in the United States, 1979-1997 - Ian Irvine; Kuan Xu (Luxembourg Income Study (LIS), 2002)
The rate of incarceration has increased dramatically in the U.S. since 1980. We explore the implications of this increased incarceration on national poverty measurement using micro data for the period 1979-1997. We make use of an as-yet unexplored data set on prisoner earnings, in conjunction with the Current Population Survey to compute earnings of the whole population. It is found that the traditional measurement of poverty, which omits this increased share of the population that has become institutionalized, understates the true degree of poverty in the nineteen nineties to a significant degree. This underestimation has increased during the time period of study. Furthermore, it is the depth of poverty associated with the higher incarceration rate, rather than the higher rate of incarceration alone that has had the greatest impact upon poverty. These results stand in marked contrast to western European economies and Canada.
Keywords: 330; Armut; Kriminalität; Strafvollzug; Strafe; USA